Feasibility, Acceptability, and Considerations for Sustainability of Implementing an Integrated Family-Based Partial Hospitalization Program for Children and Adolescents with Mood Disorders. Issue 4 (1st October 2020) - Leffler, Jarrod M.; Junghans-Rutelonis, Ashley N.; McTate, Emily A.
ABSTRACT: There are many clinically effective outpatient psychosocial treatments for youth with mood disorders, and many of them include engaging caregivers in treatment. Despite the prevalence and severity of impairment related to mood disorders, there is a dearth of research addressing implementing evidence-based treatment (EBT) models for youth with mood disorders in intensive outpatient programs (IOP) or partial hospitalization programs (PHP). The current study provides preliminary results on the feasibility, acceptability, considerations for sustainability, and consumer satisfaction of youth and their caregivers who attended the Child and Adolescent Integrated Mood Program (CAIMP), a two-week family-based PHP for youth ages 9–18 with mood disorders. The feasibility, acceptability, and sustainability of CAIMP are addressed by reviewing access, utilization, insurance coverage, and participant satisfaction. High attendance and low attrition rates were found. Youth and caregivers reported positive outcomes of attending the program as a family unit. Access, utilization, and patient insurance coverage were favorable and suggest the potential for program sustainability. Preliminary results suggest a two-week family-based PHP is accepted and tolerated by youth and their caregivers, referred to by a range of providers, and supported by a variety of payor sources. Youth and caregivers reported positive elements of the program. The current PHP model shows promise for being an important addition to the treatment options for youth with severe mood disorders and their families.